2015
DOI: 10.2514/1.j053713
|View full text |Cite
|
Sign up to set email alerts
|

Sound and Sources of Sound in a Model Problem with Wake Interaction

Abstract: Aeroacoustic predictions of a model airframe noise problem are conducted to assess the effects of wake interaction on flow and acoustic fields. Simulations of unsteady low Reynolds number flows, including both noise generation and its subsequent propagation to the far field, are performed for a configuration composed of a cylinder placed above a NACA 0012 airfoil. An assessment of cylinder position and freestream Mach number effects on sound radiation is presented. It is observed that intense interference amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Greschner et al [18], and later Giret et al [19], have pointed out that the quadrupolar sound emitted by a rod airfoil configuration at M = 0.2 was no longer negligible and that the permeable formulation better matched the experimental results of Jacob et al [20] at high frequencies for an integration surface surrounding the whole rod-airfoil system and a portion of its wake. Wolf et al [21], supported by Yu & Lele [22], have shown that in the case of a wake interaction, quadrupolar noise emission was mainly concentrated in the high frequency range. They found that it could be neglected for a Mach number of 0.1, but not for 0.3 and 0.5.…”
Section: Introductionmentioning
confidence: 93%
“…Greschner et al [18], and later Giret et al [19], have pointed out that the quadrupolar sound emitted by a rod airfoil configuration at M = 0.2 was no longer negligible and that the permeable formulation better matched the experimental results of Jacob et al [20] at high frequencies for an integration surface surrounding the whole rod-airfoil system and a portion of its wake. Wolf et al [21], supported by Yu & Lele [22], have shown that in the case of a wake interaction, quadrupolar noise emission was mainly concentrated in the high frequency range. They found that it could be neglected for a Mach number of 0.1, but not for 0.3 and 0.5.…”
Section: Introductionmentioning
confidence: 93%
“…For those applications where quadrupoles are relevant (see, for instance, the studies on the noise radiated by wakes of subsonic flows by Wolf et al [53,54]), Di Francescantonio [55] proposed changing f to a permeable moving surface moving at a velocity v i = 0 that encloses all the volumetric sources producing non-negligible noise instead of using the body surface. Equation (7) can then be rearranged to include the terms accounting for the evaluation of the noise sources in the permeable surface:…”
Section: Far-field Noise Predictionmentioning
confidence: 99%
“…In this study, we use compressible direct numerical simulations (DNS) in a generalized curvilinear coordinate and conservative form (Wolf et al. 2015). The numerical method uses a sixth-order compact scheme implemented on a staggered grid for spatial discretization (Nagarajan, Lele & Ferziger 2003).…”
Section: Numerical Simulationmentioning
confidence: 99%